Research focus and thematic trends in magnet hospital research: A bibliometric analysis of the global publications. (15th January 2021) - Yang, Weimei; Liu, Yu; Zeng, Tieying; Wang, Ying; Hao, Xinying; Yang, Weiqiang; Wang, Hui
Abstract: Aims: The study aims to carry out a bibliometric analysis of the research on magnet hospital from 1988‐2020. Design: A statistical and visualization bibliometric analysis was conducted between February‐May 2020. Methods: The information was extracted from Web of Science by the topic advanced search strategy. HistCite‐Pro, Excel, GunnMap, BibExcel and VOSviewer were used to extract, integrate and visualize the bibliometric information. Furthermore, the research contents of the core‐authors were explored and summarized by reviewing all the published articles. Results: Articles ( N = 396) published in 107 journals were retrieved in the Web of Science from 1988‐2020. The USA ( N = 319) and University of Pennsylvania ( N = 38) were the most productive country and institution respectively. Author co‐citation and bibliographic‐coupling network analysis identified that Aiken, Kramer, Laschinger, Schmalenberg, Lake and Johantgen were the major contributors and leaders in this field. According to the research content of the main contributors and keyword co‐occurrence analysis result, the research focus could be divided into four parts: the mechanism leading to the outcomes differences for magnet hospital, the evidence‐based practice, the outcomes comparison between magnet hospital and non‐magnet hospital and the practice environment. Conclusion: This bibliometric study offered a comprehensive overview of current study status of magnet hospital and this area has been drawn increasing attention over the years. However, the research on magnet hospital is still relative limited and needs to be paid more attention, especially in developing countries. Impact: This study showed the most contributed countries, journals, institutions, authors and the main themes related to magnet hospital, which would help researchers find potential partners, optimize and deepen future research, such as enhancing the magnet hospital research in developing countries, improving the evidence‐based research and considering the impact caused by different culture. Furthermore, this study can also give suggestions for magnet hospital policy makers. 摘要: 目的: 本研究旨在对磁性医院在1988‐2020年间的研究进行文献计量分析。 设计: 2020年2月至5月期间, 进行统计和可视化文献计量分析。 方法: 通过主题高级搜索策略从科学网中提取信息。利用HistCite‐Pro、Excel、GunnMap、BibExcel和VOSviewer提取、整合和可视化文献计量信息。此外, 回顾已发表的论文, 依此对核心作者的研究内容进行探讨和总结。 结果: 1988‐2020年间, 在科学网上检索出107种期刊上发表的文章 ( N =396) 。美国 ( N =319) 和宾夕法尼亚大学 ( N =38) 分别是期刊发表数最多的国家和机构。根据多个作者引用和文献耦合网络分析, 可得出结论: Aiken、Kramer、Laschinger、Schmalenberg、Lake和Johantgen是这一领域的主要贡献者和领导者。根据主要贡献者的研究内容和关键词共现分析结果, 研究重点可划分为四个部分, 分别是: 造成磁性医院结果差异的机制、循证实践、磁性医院与非磁性医院疗效比较以及实践环境。 结论: 本文献计量学研究对磁性医院的研究现状进行全面综述, 并且, 这一领域受到越来越多的关注。然而, 目前国内外对磁性医院的研究相对有限, 需要各方进一步重视, 特别是发展中国家的重视。 影响: 本研究显示了贡献最大的国家、期刊、机构、作者以及与磁性医院相关的主要主题, 有助于研究者寻找潜在的合作伙伴, 优化和深化未来研究内容, 例如, 加强发展中国家磁性医院的研究, 提高循证研究的水平, 考虑不同文化造成的影响等。此外, 可通过本研究为医院政策制定者提供建议。